INTEGRATING ARTIFICIAL INTELLIGENCE TOOLS TO ENHANCE CREATIVE EXPRESSION IN CONTEMPORARY VISUAL ARTS - Mhatre, Amruta; Gudadhe, Manish B.; Bhise, Suhas; Ahmed, Gousia; Le, Baoxin; B, Damodaran; S, Uma (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The use of the Artificial Intelligence (AI) in the field of contemporary visual art has had an impact of monumental proportions regarding the way in which the artistic production is conducted, enabling artists to experiment with the ways of expression, communication as well as even innovation. In this paper, the author speaks about the possible uses of AI-based technology to develop the creativity of the human mind and reinvent the artistic process, including Generative Adversarial Networks (GANs), diffusion models and neural style transfers. The paper provides a detailed theoretical framework, which is founded on computational creativity, human-AI co-creation paradigms and cognitive-aesthetic principles, and describes the ways in which intelligent systems are able to become collaborative participants and not mere tools. The paper will provide a detailed analysis of the existing AI technologies to demonstrate the fact that they may be utilized to create high-quality visual materials, enhance stylistic diversity, and shorten the design cycle. The results indicate that AI-based art systems can be used to facilitate the efficiency of the creative process, expand creativity opportunities, and allow people to create works of art. However, the questions of the computational complexity, the bias of the data and the ownership by law remain to be crucial problems. The future of research directions is also discussed in the paper with an aim of creating an ethical, scalable, and artist-oriented AI system. Overall, this article is bound to demonstrate the transformational ability of AI in the contemporary realms of visual arts and approach a moderate course that will not eradicate the human originality and artist intent.